1997
DOI: 10.1016/s0145-2134(97)00064-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for disruption in primary caregiving among infants of substance abusing women

Abstract: Objective-To identify perinatal factors that are predictive of disruption in primary caregiving among infants of substance abusing women.Method-A randomized longitudinal cohort study. One hundred and fifty two mother/infant dyads were assessed for evidence of disruption of primary caregiving or neglect during the first 18 months of life, defined by mother's inability to provide care. Data analyzed included neonatal characteristics, urine toxicology at delivery, maternal history of drug use, maternal depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 50 publications
5
62
0
1
Order By: Relevance
“…Pregnancy should bring the woman into contact with the health care system and may provide a 'window of opportunity' to engage the vulnerable and 'high risk' woman into essential health care (Nair et al, 1997). Many women with problematic drug use first come to the attention of treatment services when they seek care during pregnancy (Corse and Smith, 1998).…”
Section: Service Provision For Pregnant Womenmentioning
confidence: 99%
“…Pregnancy should bring the woman into contact with the health care system and may provide a 'window of opportunity' to engage the vulnerable and 'high risk' woman into essential health care (Nair et al, 1997). Many women with problematic drug use first come to the attention of treatment services when they seek care during pregnancy (Corse and Smith, 1998).…”
Section: Service Provision For Pregnant Womenmentioning
confidence: 99%
“…These findings are striking because not only did we use maternal affirmation plus positive toxicology screens to confirm PDE status, but we recruited a community comparison group that represented families who resided in the same low-income communities as the PDE children and had experienced many of the same environmental challenges associated with poverty, but had not experienced PDE or the early caregiver disruptions that frequently occur among drug using families. 35 Our analyses suggested that the perinatal, maternal, and family covariates, selected on the basis of developmentalecological theory, explained more variance in early child functioning than a history of PDE.…”
Section: Discussionmentioning
confidence: 76%
“…Substance-using street youth may be more likely to abuse their children and lose parenting rights. 15,16 Children born into street living suffer tremendous adversity, including poor physical health, mental and behavioral problems, developmental delays, as well as social stigma and the potential for family separation. 17 Official registration of birthwhich is critical for access to government-supported services, including medical care and school enrollment-may be unavailable.…”
Section: Introductionmentioning
confidence: 99%